UK community prevalence of knee chondrocalcinosis: evidence that correlation with osteoarthritis is through a shared association with osteophyte - Neame, R L; Carr, A J; Muir, K; Doherty, M (Annals of the rheumatic diseases, 2003)
Objectives: (1) To estimate the prevalence of chondrocalcinosis (CC) in the community and to characterise its compartmental distribution within the knee. (2) To investigate the associations between CC and individual radiographic features of osteoarthritis (OA) at the tibiofemoral joint (TFJ) and patellofemoral joint (PFJ). Methods: From three community questionnaire studies investigating the prevalence of knee pain, standing anteroposterior and skyline radiographs were obtained on 1727 subjects (1084 women, 643 men; mean age 63.7; 999 (58%) with knee pain). A single observer recorded the presence and site of CC and graded osteophyte and joint space narrowing (JSN) using a line atlas. “OA” was globally defined as the presence of definite osteophyte and definite JSN. Minimum joint space width (JSW) was measured to 0.1 mm with a metred dial caliper Results: (1) The crude prevalence of CC was 7.0% (95% confidence interval (CI) 5.8 to 8.2). This showed a strong association with age. The age adjusted odds ratio (aOR) for CC in women v men was 0.79 (95% CI 0.52 to 1.12). The age, sex, and knee pain standardised estimate for those aged >40 in Nottingham, UK was 4.5%. Patellofemoral CC was seen in only nine cases, all with tibiofemoral CC. (2) The age-sex aOR for the association between CC and OA was 2.08 at the PFJ (1.38 to 3.12) and 2.00 (1.11 to 3.60) at the TFJ. There was no association between measured JSW and CC at either the PFJ or TFJ. Both total osteophyte score and total number of sites with osteophyte were positively associated with CC; aOR for the upper quartile was 2.40 (1.48 to 3.90) and 1.94 (1.15 to 3.26), respectively. An association between CC and diuretic use was also demonstrated (aOR=2.07, 1.02 to 4.19). Conclusions: In this large UK community study the age, sex, and knee pain adjusted prevalence of CC was 4.5%. There was a strong age association, but no sex predisposition. Patellofemoral CC was uncommon. An association between OA and CC was confirmed, but this appears to operate through an association with osteophyte rather than JSN. The new association between CC and diuretic use might theoretically be explained by diuretic induced hypomagnesaemia.